Artistry as a necessary component of a teacher's pedagogical professionalism - Dementieva, T. (New Collegium, 2022)
The article considers the essence of the concept of "pedagogical artistry" as an important component of a teacher's pedagogical skill. That is why the training of pedagogical personnel is so important, as a result of which they must master a high level of professional competence, methodological thinking, general and professional culture, professionally significant personality qualities, and a creative approach to teaching and education. Integrating, these qualities form the teacher's pedagogical skill, which ensures a high level of his professional and pedagogical activity on a reflective basis. The fulfillment of this historic mission in the training of pedagogical personnel, so that students mastered the special art of teaching and educating others and self-learning throughout life, was directed by an outstanding scientist, a well-known specialist in the field of new pedagogical technologies of learning and education, economic theory, philosophy of education, the rector of the Kharkiv National Pedagogical University named after G. S. Skovorody from 1980 to 2020 Ivan Fedorovich Prokopenko. He believed that every teacher should possess a set of personal qualities that ensure a high level of self-organization of a teacher's professional activity. Among these qualities, artistry occupies a special place as one of the important professional components. Summarizing the views of the authors on the definition of this phenomenon, it was concluded that the teacher's pedagogical artistry is a high level of pedagogical activity, which is manifested in the teacher's ability to vividly, emotionally, uniquely convey the educational material, using all his experience, competence and pedagogical technologies. The professional activity of a teacher should include not only friendly communication, harmony of mind and feelings, but also pedagogical mastery at the level of art, which is ensured by a high degree of development of professionally necessary qualities, abilities, skills and, in particular, pedagogical artistry. Therefore, the formation of pedagogical artistry is one of the tasks of training. The result of artistic teaching is the formation of students' motivational and valuable attitude to the content of education. Emotional perception of the material contributes to maintaining sustained attention and interest, deepening the motives of educational cognition, in response to the desire to open up.